Effect of different depths of irrigation water on yield and water use pattern of summer groundnut (Arachis hypogaea L.): EFFECT OF DEPTHS OF IRRIGATION WATER ON YIELD AND WATER USE PATTERN OF GROUNDNUT - AMAR NATH MALLIC; SUNIL KUMAR GUNR; SRIJITA PAUL; MANASHI BARMAN; ASISH MUKHERJEE; AMRITA SENGUPTA (Journal of Oilseeds Research, 2018)
Field experiment was conducted during summer season of 2013 and 2014 to evaluate the effect of different depths of irrigation water on yield and water use pattern of summer groundnut. Plant height increased with increasing the quantity and uniform depth (50 mm) of irrigation water during all through growth period. Towards maturity presence of moisture had no greater influence to plant growth but had significant role to developmental processes. Depth ofirrigation had greatly influenced on drymatter production rather than total quantity of irrigation water applied. Increasing irrigation depth to higher (40 mm) from lower (20 mm) depth did not influence the crop growth rate significantly. Irrigation water applied either uniform or different depth during various growth stages significantly influenced the yield attributes viz., number of pods per plant, shelling percentage etc. and skipping of irrigation water at any stage did not influence the yield attributes. Yield of groundnut also increased with lesser quantity of irrigation water when irrigation water was applied in judicious manner with different depths during different growth stages. Skipping of any depth of irrigation water from 30 DAE to 65 DAE the pod yield was reduced significantly about 20-26 per cent and moisture stress at early growth stage to early pod development stage was detrimental. Total water use or water expense was higher under T7 (379.0 mm) where 160 mm irrigation water was applied under various depths during different growth stages followed by skipping of 20 mm irrigation water at 30 DAE but water expense efficiency was higher under T5 where, 180 mmofirrigation water was applied in different depth of combinations during different growth stages of the crop followed by higher pod yield. So it may be concluded that moisture stress at early growth stage to early pod development stage was detrimental and to meet the physiological demand of the crop judicious management of irrigation water viz., shallow depth of irrigation water at early part of the growth along with medium depth of irrigation water towards later growth stages (T5) is recommended for good harvest of the crop.